2018
DOI: 10.1519/jpt.0000000000000203
|View full text |Cite
|
Sign up to set email alerts
|

Stand Tall—A Virtual Translation of the Otago Exercise Program

Abstract: Results support that an avatar-delivered version of the OEP is effective, feasible, viable, and enjoyable for community-dwelling older adults. These types of platforms should be considered as potential mechanisms to increase availability of fall prevention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
4
13
0
Order By: Relevance
“…Previous studies revealed that an 8-week OEP intervention in a group-based setting significantly improved functional balance48 assessed with the BBS. Our results showed an improvement in functional balance similar to that reported by longer OEP interventions (by 3.2 to 5.3 points) lasting 4 to 6 months 18,20,50.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies revealed that an 8-week OEP intervention in a group-based setting significantly improved functional balance48 assessed with the BBS. Our results showed an improvement in functional balance similar to that reported by longer OEP interventions (by 3.2 to 5.3 points) lasting 4 to 6 months 18,20,50.…”
Section: Discussionmentioning
confidence: 97%
“…Internet-based translations can be effective and they can overcome geospatial barriers if modifications adhere to the critical elements of the original intervention and are made accessible and affordable to underserved areas. While interventions like OEP have been successfully translated for online delivery (i.e., Stand Tall) [50], additional programs, such as AMOB and SO, are currently undergoing virtual translation. Further, SAIL and OEP have online training available, which addressed the cost- and travel-related concerns that are associated with getting trained face-to-face.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the improved OEP gradually became efficient and feasible. Through the training of professional physiotherapists and combined with virtual technology, its feasibility and scientificity were ensured ( 11 , 21 ). OEP has been widely used in clinical rehabilitation and postoperative recovery.…”
Section: Resultsmentioning
confidence: 99%